Aesthetic Evaluation and Validation: Umbilicus Reconstruction after DIEP Flap - Haddock, Nicholas T.; Steppe, Cyrus; Teotia, Sumeet S. (Journal of Reconstructive Microsurgery, 2023)
Background The most common method for autologous breast reconstruction is the deep inferior epigastric perforator (DIEP) flap. The umbilicus can be managed in various ways, including re-inset, neoumbilicus, and umbilectomy without reconstruction. This study evaluated the aesthetic differences in umbilicus reconstruction choice and variation in patients' postoperative satisfaction with their abdomen.Methods A retrospective review of 1,019 patients treated with DIEP flap breast reconstruction between August 2009 and January 2022 was conducted. Patients were stratified by management of the umbilicus: preservation and re-inset of the native umbilicus, umbilectomy with delayed reconstruction, and umbilectomy with no reconstruction. A crowdsourced survey was created to assess the aesthetic preference of each photograph using a Likert scale.Results There were 1,063 responses to the umbilicus preference crowd source survey. Patients who had delayed umbilicus reconstruction after umbilectomy were rated to be significantly more attractive (4.397 ± 1.697) than both preservation of the native umbilicus (4.176 ± 1.669) and lack of the umbilicus (3.994 ± 1.733; p < 0.001 and <0.001, respectively). In an analysis of the BREAST-Q scores, delayed reconstruction patients had a similar change across measures when compared to the re-inset group. The delayed group had a significantly higher change in overall satisfaction and well-being with abdomen when compared with the no reconstruction group (p = 0.006 and 0.027, respectively).Conclusion This study demonstrates that umbilectomy with delayed reconstruction yields a significantly higher aesthetic rating and comparable patient satisfaction when compared to re-inset of the umbilicus.
Keywords: autologous; DIEP; umbilicus